2020
DOI: 10.1021/acs.jafc.0c06132
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Fruit-Derived Flavanone Glycoside Narirutin is a Novel Potent Inhibitor of Organic Anion-Transporting Polypeptides

Abstract: Organic anion-transporting polypeptides (OATPs) 1A2 and OATP2B1 are expressed in the small intestine and are involved in drug absorption. We identified narirutin, which is present in grapefruit juice, as a novel OATP inhibitor. The citrus fruit jabara also contains high levels of narirutin; therefore, we investigated the inhibitory potency of jabara juice against OATPs. The inhibitory effects of various related compounds on the transport activity of OATPs were evaluated using OATP-expressing HEK293 cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Moreover, OATP1A2‐mediated fexofenadine uptake was nearly completely inhibited in the presence of EGCG (100 μM and 1 mM) or GTE (0.1 and 1 mg/mL; P < 0.01; Figure ). On the other hand, only slight but significant uptake of fexofenadine (10 μM) mediated by OATP2B1 was observed in HEK‐OATP2B1 cells compared with vector control cells at both pH 6.3 and pH 7.3 ( Figure ), which is in accordance with recent papers 29,30 . However, due to low uptake ratio for OATP2B1‐mediated fexofenadine transport, inhibition studies at both pH conditions revealed no consistent effect for both EGCG and GTE (data not shown).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Moreover, OATP1A2‐mediated fexofenadine uptake was nearly completely inhibited in the presence of EGCG (100 μM and 1 mM) or GTE (0.1 and 1 mg/mL; P < 0.01; Figure ). On the other hand, only slight but significant uptake of fexofenadine (10 μM) mediated by OATP2B1 was observed in HEK‐OATP2B1 cells compared with vector control cells at both pH 6.3 and pH 7.3 ( Figure ), which is in accordance with recent papers 29,30 . However, due to low uptake ratio for OATP2B1‐mediated fexofenadine transport, inhibition studies at both pH conditions revealed no consistent effect for both EGCG and GTE (data not shown).…”
Section: Resultssupporting
confidence: 89%
“…This was confirmed in BSP transport assay for OATP2B1 ( Figure ). On the other hand, only slight uptake of fexofenadine was observed in HEK‐OATP2B1 cells at pH 6.3 and pH 7.3, which is in accordance with recently published data 29,30,41 . Due to low uptake ratio (HEK‐OATP2B1/HEK‐Co), we found no consistent effects of GTE and EGCG on OATP2B1‐mediated fexofenadine transport.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, jabara (Citrus jabara) juice was found to contain considerable levels of narirutin but not naringin. 23 However, the inhibitory effects of other fruit juices on OATPs have yet to be determined, and certain juices may cause drug interactions with OATP substrates via OATP inhibition. Therefore, it is clinically important to comprehensively assess the inhibitory effects of various fruit juices on OATPs.…”
Section: ■ Introductionmentioning
confidence: 99%